2019
DOI: 10.1029/2019gl085158
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Shallow Low‐Frequency Earthquakes off the Kii Peninsula, Japan, in 2004 Revealed by Ocean Bottom Seismometers

Abstract: The characteristics of shallow low-frequency earthquakes (LFEs) are related to stress changes on the shallow plate boundary, which are important for understanding the megathrust earthquake cycle. The 5 September 2004 off the Kii Peninsula earthquakes (M JMA = 7.1, 7.4) occurred near the Nankai trough subduction zone, off southwest Japan. Ocean bottom seismometer observations from 22 September to 30 November 2004 detected many shallow LFEs among the ordinary aftershocks. During the observation period, the frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…Because we did not introduce a small-scale velocity heterogeneity into the reference model in this simulation, we confirmed that the 10 shallower heterogeneities, such as seawater and the thick low-velocity accretionary prism, also distorted the maximum amplitude distribution. Thus, the assumption of isotropic radiation for energy estimations of small offshore seismic events in many studies could be suitable (e.g., Tamaribuchi et al, 2019;Yabe et al, 2019). Because our simulations did not include site amplifications caused by structures with VS < 0.5 km/s, the observed maximum amplitude distribution could be more complicated because of site amplification factors at DONET stations for high-frequency seismic waves (e.g., Kubo et al, 2018;Yabe et al, 2019).…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because we did not introduce a small-scale velocity heterogeneity into the reference model in this simulation, we confirmed that the 10 shallower heterogeneities, such as seawater and the thick low-velocity accretionary prism, also distorted the maximum amplitude distribution. Thus, the assumption of isotropic radiation for energy estimations of small offshore seismic events in many studies could be suitable (e.g., Tamaribuchi et al, 2019;Yabe et al, 2019). Because our simulations did not include site amplifications caused by structures with VS < 0.5 km/s, the observed maximum amplitude distribution could be more complicated because of site amplification factors at DONET stations for high-frequency seismic waves (e.g., Kubo et al, 2018;Yabe et al, 2019).…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Around the Japanese Islands, permanent OBS networks of DONET and S-net (National Research Institute for Earth Science and Disaster Resilience, 2019c, 2019a) have been recently deployed. Several studies have used temporal OBS data or such permanent networks to estimate the source characteristics of small earthquakes and shallow low-frequency tremors (LFTs) (e.g., Nakano et al, 2015Nakano et al, , 2019Nishikawa et al, 2019;Tamaribuchi et al, 2019;Tanaka et al, 2019;Yabe et al, 2019). Offshore 3D heterogeneities, seawater, and bathymetry significantly affect seismic wave propagation even for low-frequency ground motions (e.g., Gomberg 2018;Guo et al 2016;Nakamura et al 2015;Shapiro et al 1998Volk et al 2017), complicated seismic waves such as T phase, Scholte, acoustic-coupled, and ocean-mode Rayleigh waves, as has been observed in previous studies (e.g., Haney & Tsai, 2017;Muyzert, 2007;Noguchi et al, 2016;Okal, 2008;Takeo et al, 2014;.…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to locate tremors in the offshore region by using an onshore network because sources of tremors are distant from the network and signals of tremors attenuate strongly compared to VLFE (0.02–0.05 Hz) signals. Based on the spatiotemporal correlation between VLFEs and tremors reported in other regions (e.g., Ghosh et al., 2015; Maeda & Obara, 2009; Tamaribuchi et al., 2019) and the interpretation that VLFEs and tremors are components of broadband slow earthquake phenomena (Gomberg et al., 2016; Hawthorne & Bartlow, 2018; Ide & Maury, 2018), we estimated the energy rate functions of tremors accompanied by VLFEs by assuming that a tremor occurs at the same location as the VLFE, that is, the VLFE source grid with the highest CC as written in Section 2.1.3 (e.g., Yabe et al., 2021). We simulated the waveforms at the location of a VLFE using the same model which is described in Section 2.1.2 but discretized by a finer grid interval (0.04 km).…”
Section: Methodsmentioning
confidence: 99%
“…Observations using self-pop-up-type ocean bottom seismometers (OBSs) detected low-frequency tremors and earthquakes in Kumano-nada (Obana and Kodaira 2006;Tamaribuchi et al 2019) and Hyuga-nada (Yamashita et al 2015). Using broadband OBSs, Sugioka et al (2012) detected sVLFEs that occurred along the plate boundary fault.…”
Section: Introductionmentioning
confidence: 99%